2015
DOI: 10.1371/journal.pone.0137207
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Containing Curcumin Useful for Suppressing Macrophages In Vivo in Mice

Abstract: To explore a novel method using liposomes to suppress macrophages, we screened food constituents through cell culture assays. Curcumin was one of the strongest compounds exhibiting suppressive effects on macrophages. We subsequently tried various methods to prepare liposomal curcumin, and eventually succeeded in preparing liposomes with sufficient amounts of curcumin to suppress macrophages by incorporating a complex of curcumin and bovine serum albumin. The diameter of the resultant nanoparticles, the liposom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…Generally, it is concluded that administering curcumin in combination with dietary fatty acids reduces ROS generation in macrophages (23). In line with this study, Amano et al showed that liposomes containing curcumin could suppress the macrophages in mice in a selective manner (24). A pathway through which curcumin may exert its suppressive effects on macrophages has been suggested to be NF-κB signaling pathway as it has been observed that this compound diminishes macrophage activation and influenza virus induced-lung inflammation by inhibiting NF-κB pathway (25).…”
Section: Immunomodulatory Effectssupporting
confidence: 71%
“…Generally, it is concluded that administering curcumin in combination with dietary fatty acids reduces ROS generation in macrophages (23). In line with this study, Amano et al showed that liposomes containing curcumin could suppress the macrophages in mice in a selective manner (24). A pathway through which curcumin may exert its suppressive effects on macrophages has been suggested to be NF-κB signaling pathway as it has been observed that this compound diminishes macrophage activation and influenza virus induced-lung inflammation by inhibiting NF-κB pathway (25).…”
Section: Immunomodulatory Effectssupporting
confidence: 71%
“…Therefore, a carefully designed carrier could significantly facilitate the drug delivery extending the potential pharmaceutical applications of curcumin. In this regard, several drug delivery systems (DDS) were recently developed, such as the curcumin loading into liposomes or nanoparticles [33]. Additionally, both curcumin-phospholipid complexes and structural analog of curcumin were successfully synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, we have examined the possible convenience to use designed carrier that could increase the drug delivery and allow for a wider applicability of curcumin in vivo. In this regard, several drug delivery systems (DDS), such as the curcumin loading into liposomes or nanoparticles, have been developed by other groups, though these are not always exploitable for clinic use due to high side effects and low efficacy [99][100][101].…”
Section: Curcuminmentioning
confidence: 99%